Perancangan Sistem Monitoring Keamanan Brankas Rumah Berbasis Internet of Things (IoT) secara Real-Time melalui Telegram Bot - Yesaya IXVois Hendrikus Sereh; Mizanul Achlaq; Agung Widodo (Journal of Engineering and Applied Technology, 2025)
This study presents the design and development of a real-time IoT-based monitoring security system for home safes integrated with Telegram Bot notifications. The proposed system employs NodeMCU ESP8266 as the main controller, combined with an HC-SR04 ultrasonic sensor for motion detection and an MPU-6500 vibration sensor for shock recognition. When suspicious movement or abnormal vibration is detected, the system activates a local buzzer alarm and triggers an automatic solenoid door lock mechanism through a relay module. Simultaneously, warning messages are transmitted instantly to users via Telegram Bot and displayed on a web-based monitoring dashboard. Experimental evaluation indicates that the ultrasonic sensor achieved an average measurement error of ±1.6 cm, while vibration detection responded within 0.2–0.5 seconds. The solenoid locking mechanism demonstrated 100% success across all test scenarios. Telegram notifications were delivered with an average latency of 1.33 seconds, depending on network quality. The optimization stage improved detection stability, reduced false alarms, and enhanced system reliability. Overall, the developed prototype offers an effective and low-cost smart security solution for domestic safe protection.